Optimal Course Scheduling Decision Support System Using CSP Method Based on Room and Lecturer Availability - Naibaho, Eltrina; Sianturi, Ronda Delli; Sirait, Matias Julius Fika; Sianturi, Anggita H. (Bahasa Indonesia, 2025)
Course scheduling is a complex and critical task for universities, as it must consider various constraints such as lecturer availability, classroom capacity, and time slot limitations. Improper scheduling can lead to inefficiencies, conflicts, and dissatisfaction among lecturers and students. This study aims to develop a Decision Support System (DSS) for optimal course scheduling at Universitas Budidarma using the Constraint Satisfaction Problem (CSP) method. CSP provides a structured approach to solve scheduling problems by defining variables, domains, and constraints, and finding solutions that satisfy all requirements. The system was designed to input course data, lecturer availability, and available classrooms, then generate a conflict-free schedule automatically. Testing results show that the CSP-based system successfully generated valid schedules that met all given constraints, reduced scheduling conflicts, and improved resource utilization. This research demonstrates that CSP is an effective method for handling complex academic scheduling tasks, supporting more efficient academic planning processes in higher education institutions.